2018
DOI: 10.1002/tcr.201800061
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Reduction of Carboxylic Acid Derivatives and CO2 by Metal Nanoparticles on Lewis‐Acidic Supports

Abstract: The development of heterogeneous catalysts for green chemical synthesis is currently a growing area in catalysis and sustainable chemistry. Especially the use of renewable carbon resources such as carbon dioxide (CO2) and biomass‐derived compounds (e. g. carboxylic acids, esters, and amides) represent highly attractive research targets. As these substances reside in a high oxidation state, efficient reduction processes are required in order to convert these substrates into useful and value‐added chemicals. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 197 publications
(197 reference statements)
1
18
0
Order By: Relevance
“…Hydrogenation reactions of carboxylic acids, esters, and amides are receiving increased attention because of their use in a variety of applications in the pharmaceutical and fine-chemical industry, as well as for upgrading bio-based chemical feedstocks. [1][2][3][4][5] Although significant progress has been made in recent years, the development of catalysts that promote these processes remains a formidable task. The difficulties are predominantly a consequence of the fact that carboxylic acid derivatives are kinetically unreactive and thermodynamically stable as a result of the low electrophilicity of the carbonyl carbons.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenation reactions of carboxylic acids, esters, and amides are receiving increased attention because of their use in a variety of applications in the pharmaceutical and fine-chemical industry, as well as for upgrading bio-based chemical feedstocks. [1][2][3][4][5] Although significant progress has been made in recent years, the development of catalysts that promote these processes remains a formidable task. The difficulties are predominantly a consequence of the fact that carboxylic acid derivatives are kinetically unreactive and thermodynamically stable as a result of the low electrophilicity of the carbonyl carbons.…”
Section: Introductionmentioning
confidence: 99%
“…Various metal oxides, namely, VO x , WO x , GaO x , ReO x , SnO x , and NbO x , were screened as Ni/TiO 2 modifiers to obtain efficient catalysts for the hydrogenation of methyl palmitate to cetyl alcohol. According to prior studies, the combination of group 5–7 metals with group 8–10 metals is beneficial to promoting the selective hydrogenation process owing to their unique synergistic effect in the hydrogenation reactions. Therefore, here, we focused on group 5–7 metal oxides as additives.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that biomass stores solar energy and contains various reductive groups such as hydroxyl, aldehyde, amino, it can be used as an ideal reductant to reduce CO 2 theoretically 58‐60 . We found that a large amount of hydrogen is generated from both glycerol gasification and water splitting during hydrothermal glycerol conversion to lactic acid 48,49 .…”
Section: Reaction Mechanism Of Hydrothermal Reduction Of Co2 Into For...mentioning
confidence: 95%
“…Considering that biomass stores solar energy and contains various reductive groups such as hydroxyl, aldehyde, amino, it can be used as an ideal reductant to reduce CO 2 theoretically. [58][59][60] We found that a large amount of hydrogen is generated from both glycerol gasification and water splitting during hydrothermal glycerol conversion to lactic acid. 48,49 These results further indicate that biomass is reductive under hydrothermal conditions, and the hydrogen could be produced from both biomass and water decomposition for efficient in situ hydrothermal reduction of CO 2 .…”
Section: Hydrothermal Reduction Of Co 2 To Formic Acid With Biomass-d...mentioning
confidence: 98%